2006
DOI: 10.1159/000092984
|View full text |Cite
|
Sign up to set email alerts
|

Salt Sensitivity and Hypertension after Menopause: Role of Nitric Oxide and Angiotensin II

Abstract: Hypertension is a major risk factor for cardiovascular disease and renal disease. After menopause, the incidence of hypertension increases in women to levels that equal or exceed that in men, suggesting a protective role of female sex hormones. Salt sensitivity of blood pressure is associated with an increased risk for development of hypertension and cardiovascular disease. We and others have demonstrated that after menopause, the prevalence of salt sensitivity increases, suggesting that female sex hormones in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 170 publications
1
27
0
Order By: Relevance
“…Several other studies support the notion that estrogen has the potential for exerting vasoprotective effects through modulation of pro-oxidant and antioxidant enzyme expression and activity by modulating the RAA and NO systems, 31 as well as enzymes such as NAD(P)H oxidase, Rho-kinase and superoxide dismutase, 32 and the transcription factor NF-kB. 33 The aforementioned findings demonstrated that in addition to the known effects on eNOS activity and expression, estrogen acts as an indirect antioxidant at the genomic level by downregulating the capacity of endothelial cells to generate reactive oxygen species, thereby improving their NO/O 2 balance.…”
Section: Role Of Estrogen In Ckdmentioning
confidence: 80%
“…Several other studies support the notion that estrogen has the potential for exerting vasoprotective effects through modulation of pro-oxidant and antioxidant enzyme expression and activity by modulating the RAA and NO systems, 31 as well as enzymes such as NAD(P)H oxidase, Rho-kinase and superoxide dismutase, 32 and the transcription factor NF-kB. 33 The aforementioned findings demonstrated that in addition to the known effects on eNOS activity and expression, estrogen acts as an indirect antioxidant at the genomic level by downregulating the capacity of endothelial cells to generate reactive oxygen species, thereby improving their NO/O 2 balance.…”
Section: Role Of Estrogen In Ckdmentioning
confidence: 80%
“…Furthermore, the development of glomerulosclerosis in rodents does not start until a stage in life that corresponds with the early menopausal period in humans. 165 Ovariectomy aggravates renal injury and causes hypertension in laboratory animals, effects that are attenuated by sex hormone treatment. Moreover, estrogens may confer renal protection by inhibiting components of the RAAS, including angiotensin type 1 receptor expression, and by reducing angiotensin-converting enzyme activity.…”
Section: Estrogens and The Kidney: Salt Sensitivity And Renal Diseasementioning
confidence: 99%
“…2,5 However, ovariectomy did not significantly affect blood pressure or renal eNOS activity in salt-resistant rats. 2,5 These findings imply that, in the presence of salt sensitivity, a loss of estrogen may impair the bioavailability of NO, thereby contributing, at least in part, to the development of hypertension.Recent clinical studies have demonstrated that 17␤-estradiol therapy lowered plasma concentrations of asymmetrical dimethylarginine ([ADMA] an endogenous NO synthase inhibitor) in healthy, normotensive postmenopausal women. 6,7 These studies did not assess whether there is a relationship among estrogen status, ADMA levels, and salt sensitivity of blood pressure.…”
mentioning
confidence: 97%
“…2,5 However, ovariectomy did not significantly affect blood pressure or renal eNOS activity in salt-resistant rats. 2,5 These findings imply that, in the presence of salt sensitivity, a loss of estrogen may impair the bioavailability of NO, thereby contributing, at least in part, to the development of hypertension.…”
mentioning
confidence: 97%